Electrical properties of a novel solid biopolymer electrolyte based on alginate incorporated with citric acid - Ahmad Faizrin, Ahmad Fuzlin; Noor Syahida, Ismail; Nagao, Yuki; Ahmad Salihin, Samsudin (DRPM Universitas Indonesia, 2019)
In the present study, a novel solid biopolymer electrolytes (SBE) system has been introduced by doping citric acid into alginate polymer. The sample of alginate-citric acid SBE system was prepared via solution casting technique. By using Electrical Impedance Spectroscopy (EIS), the electrolytes of alginate-citric acid has been analyzed from 5 Hz to 1 MHz achieved highest conductivity value at 20 wt.% of 5.49 x 10-7 S cm-1. The temperature dependence of various composition citric acid was found to obey the Arrhenius rules with R2~1 where all SBE system is thermally activated when increasing temperature. The dielectric studies of the alginate-citric acid SBE system showed a non-debye behavior based on data measured using complex permittivity (ε*) and complex electrical modulus (M*) at selected temperature where there are no single relation was found in new biopolymer electrolytes system.